Adaptation of GRI Standards and Creation of USR Indicators: A Joint Effort between Universitat de Barcelona and Universitat Pompeu Fabra - Corretgé Bergua, Roser (2018)
This paper looks into the lack of single and specific indicators in relation to university social responsibility, and into the limitations of models for the preparation of sustainability reports applied to universities. It begins with an analysis of the growing importance of University Social Responsibility and the reasons why it is considered appropriate to create a specific model for universities that produce sustainability reports. This research is limited to a case study of the processes carried out by two universities in Barcelona to adapt the standards of the Global Reporting Initiative (GRI) to their own organizational reality, detailing the creation process of new indicators that should make possible the production of higher-quality sustainability reports, given the fact that they are more in line with the university reality. The initial results for the indicators’ adaptation are presented, and some lines of discussion are suggested to promote the universities’ participation in the creation of a unitary framework that would allow the evaluation of performance towards continuous improvement.